Anatomical and physiological aspects of the central and peripheral nervous system - Шерстюк, Сергій Олексійович; Гафт, Костянтин Леонідович; Сидоренко, Руслан Валеріанович; Погребняк, Анна Олександрівна; Scherstiuk, S.; Gaft, K.; Sydorenko, R.; Pogrebnyak, A. (Харків : ХНУ имени В. Н. Каразіна, 2023)
Human anatomy and Physiology is the science of structure of biological organisms and life processes, the activity of individual organs and a living organism. The subject of these two sciences are the parameters of the living organism, for physiology, these are the functions of the body, their relationships, regulation and adaptation to the environment, for anatomy, these are the morphological features of the individual as a whole and in the process of evolution during individual development. This discipline is designed to combine the existing knowledge of human anatomy and physiology, to give the highest understanding of the existence of biological matter, to form the foundation for medical tactics in the medical practice of a future doctor
Анатомо-фізіологічні аспекти центральної та периферичної нервової системи
Methodical recommendations for students in course «Anatomical and physiological aspects of the central and peripheral nervous system» are developed in accordance with the current programs in physiology for students of medical faculties of universities. The manual is designed for students in preparation for the course «Anatomical and physiological aspects of the central and peripheral nervous system». Each topic contains a list of practical skills and control questions. The topics are illustrated with drawings and diagrams that facilitate the perception of the material and promote its better assimilation. The materials allow students to form a correct understanding of the laws of the human body. For medical students
Keywords: central nervous system; synapses; motor functions; spinal cord; brainstem; body functions; somato-sensory system; peripheral nervous system; периферична нервова система; сомато-сенсорна система; функції організму; стовбур головного мозку; спинний мозок; рухові функції; центральна нервова система; синапси